Introduction to scientology [videorecording] : L. Ron Hubbard - Hubbard, L. Ron [ (La Fayette Ron)] , 1911-1986; Hitchman, Tony (Golden Era Productions, 2006)
An interview with L. Ron Hubbard, in which he discusses the origins and practice of Scientology and Dianetics